The Influence of Brand Image, E-WOM, and Product Quality on Repurchase Decisions Mediated by Customer Satisfaction - I Made Indra Widyadnyana; I Nyoman Rasmen Adi (Eduvest - Journal of Universal Studies, 2026)
This research examines the role of brand image, E-WOM, and product quality on repurchase decisions mediated by customer satisfaction. Conducted at Chatime outlets in Bali Province, it targeted all Chatime customers using accidental sampling (n=105). Data from a 5-point Likert scale questionnaire were analyzed via PLS-SEM. Findings show brand image, E-WOM, and product quality positively influence Chatime beverage repurchase decisions. Customer satisfaction significantly mediates brand image–repurchase (coefficient = 0.298, T-statistic = 2.382, p = 0.009) and product quality–repurchase relationships (coefficient = 0.202, T-statistic = 1.888, p = 0.030), via pathways where positive perceptions foster satisfaction leading to repurchases. However, it does not mediate E-WOM–repurchase (coefficient = 0.007, T-statistic = 0.155, p = 0.438), indicating direct cognitive effects. Notably, satisfaction mediates brand image and product quality effects but not E-WOM. The study advances literature and aids Chatime in boosting loyalty and satisfaction.